Feasibility study of integrating maternal nutrition interventions in existing maternal, newborn and child health services - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Findings helped inform the relevance and adoptability of BCC strategies that are currently being used in Alive & Thrive. Developed tools for a nested cohort study for collecting objective measures of the key outcomes (maternal weight gain during pregnancy, consumption of iron folic acid (IFA) and calcium supplements, diet diversity)